A new Defective Helper RNA to produce recombinant Sindbis virus that infects neurons but does not propagate - Justus M Kebschull; Justus M Kebschull; Pedro eGarcia da Silva; Anthony M Zador (Frontiers Media S.A., 2016)
Recombinant Sindbis viruses are important tools in neuroscience because they combine rapid and high transgene expression with a capacity to carry large transgenes. Currently, two packaging systems based on the DH(26S)5'SIN and the DH-BB(tRNA;TE12) Defective Helper (DH) RNAs are available for generating recombinant Sindbis virus that is neurotropic (able to infect neurons and potentially other cells). Both systems produce a fraction of viral particles that can propagate beyond the primary infected neuron. When injected into mouse brain, viruses produced using these DH RNAs produce transgene expression at the injection site, but also elsewhere in the brain. Such ectopic labeling caused recombinant Sindbis viruses to be classified as anterograde viruses with limited retrograde spread, and can complicate the interpretation of neuroanatomical and other experiments.Here we describe a new DH RNA, DH-BB(5'SIN;TE12ORF), that can be used to produce virus that is both neurotropic and propagation-incompetent. We show in mice that DH-BB(5'SIN;TE12ORF)-packaged virus eliminates infection of cells outside the injection site. We also provide evidence that ectopically labeled cells observed in previous experiments with recombinant Sindbis virus resulted from secondary infection by propagation-competent virus, rather than from inefficient retrograde spread. Virus produced with our new packaging system retains all the advantages of previous recombinant Sindbis viruses, but minimizes the risks of confounding results with unwanted ectopic labeling. It should therefore be considered in future studies in which a neurotropic, recombinant Sindbis virus is needed.